Factors associated with progression of atrial fibrillation and impact on all-cause mortality: an ancillary analysis from the ESC-EHRA EURObservational Research Programme in Atrial Fibrillation General. (3rd October 2022) - Vitolo, M; Proietti, M; Bonini, N; Romiti, G F; Fauchier, L; Marin, F; Nabauer, M; Potpara, T S; Dan, G A; Kalarus, Z; Tavazzi, L; Maggioni, A P; et al.
Abstract: Background: Paroxysmal atrial fibrillation (AF) often shows a natural progression towards more sustained forms of the arrhythmia. Real-world data on clinical factors associated to AF progression and its impact on long-term outcome are limited. Purpose: To investigate the factors associated with progression of AF and its impact on all-cause mortality in a contemporary cohort of European AF patients Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. Patients with paroxysmal AF at baseline or first detected AF who underwent successful cardioversion were included. Patients with known rhythm status at 1-year were then stratified into two groups: (i) No AF progression and (ii) AF progression (as defined by transition to persistent or permanent AF). All-cause mortality at 2-year of follow-up was the primary outcome of the analysis. Results: A total of 2688 patients were included (median age 67 years, interquartile range [IQR] 60–75, females 44.7%, CHA2DS2VASc score median 3 [1–4], HASBLED median 1 [1–2]). After 1-year of follow-up 2094 (77.9%) patients showed no AF progression while 594 (22.1%) developed AF progression. On multivariable logistic regression analysis, no physical activity (odds ratio [OR] 1.35, 95% confidence interval [CI] 1.02–1.78), valvular heart disease (OR 1.63, 95% CI 1.23–2.15), left atrium diameter (OR 1.03, 95% CI 1.01–1.05) and left ventricular ejection fraction (OR 0.98, 95% CI 0.97–1.00) were independently associated with AF progression at 1-year. At the end of 2-year of follow-up, death occurred in 80/2621 (3.1%) patients. Kaplan-Meier analysis showed a lower cumulative survival from all-cause mortality in patients with AF progression compared to non-progression AF patients (Log Rank p=0.01, Figure 1). On multivariable Cox regression analysis, adjusted for age, sex, heart failure, coronary artery disease, hypertensions, diabetes mellitus, previous thromboembolic events, peripheral artery disease, chronic kidney disease and use of oral anticoagulants, patients with AF progression had an independently higher risk for all-cause mortality (adjusted hazard ratio [aHR] 1.77, 95% CI 1.09–2.89). Conclusions: In a contemporary cohort of European AF patients, a substantial number of patients progressed to sustained AF within 1 year. Clinical factors related to atrial structural remodeling were independently associated with arrhythmia progression. AF progression was associated with an increased risk of all-cause mortality. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022).